Hubungan Tingkat Pengetahuan dengan Penyesuaian Diri Remaja Putri Menghadapi Masa Pubertas Di SMP Darul Hijrah Putri Banjarbaru Tahun 2013 - Agus Rahmadi; Rika Vira Zwagery; Ariani Ariani; STIKES Husada Borneo; Dinas Kesehatan Kota Banjarbaru; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2014)
Adolescence is a transitional period between childhood toward adulthood where there growth spurt (growth spurt) physically and psychologically. Entering adolescence will be preceded by the occurrence of sexual maturity. Teens will be faced with circumstances that require adjustments to be able to accept the changes that happened to him. Negative responses about physical changes in adolescents can lead to various effects such as feeling embarrassed, did not want to hang out, feeling awkward with a new look. The purpose of this study was to determine the relationship of the level of knowledge with self adjusting puberty in girls junior Darul Hijrah Banjarbaru. Types with cross sectional analytic study. The samples in this study were 100 student girls in junior high school DarulHijrah. The results showed that the level of knowledge about puberty girls are in categories A total of 47%. Adjustment teenage girls at puberty is having a negative behavior as much as 61%. Analysis using chi-square test to get the value p = 0.001 <Î± 0.05. There is a relationship with the knowledge level adjustment teenage girls facing puberty in junior Darul Hijrah Banjarbaru. suggestion to young women to further increase the knowledge about puberty so it can adapt to meet the physical changes that are being experienced.